The creative potential of contemporary Russian political discourse: From new words to new paradigms - Natalia V. Kozlovskaya; Andrey V. Rastyagaev; Julia V. Slozhenikina (Peoples' Friendship University of Russia (RUDN University), 2020)
This paper analyses the creative potential of Russian political discourse in 2010-2020. The authors outline the range of lexemes making up Russian political lexicon and draw conclusions on their relevance based on their increased importance for social life, their frequency of use in spoken and written communication and their discursive migration. Creativity is viewed as one of the characteristics of linguistic consciousness. Increased creativity in political discourse may be explained by the constant dynamics of language and the process of active word derivation. The material under analysis is taken from the digital neological database of the Department of Lexicography of the Contemporary Russian Language at the Institute for Linguistic Research of the Russian Academy of Sciences that contains about 110,000 words. The linguistic material was collected from the Integrum electronic mass media archive. The authors singled out the following language processes that enable realising the creative potential of political neologisms: the ludic use of word-building resources; the activation of noun-based word-formation; and determinologisation accompanied by a change in the term's frame structure. Specific ways of fulfilling creative potential include the use of suffixes and word-building (e.g. the creation of hyphenated complexes and multi-root words). In the period under consideration, many of these new words in Russian political discourse have become part of Internet memes.